THE HYGIENIC ROLE OF INDOOR PLANTS IN IMPROVING THE QUALITY OF THE AIR ENVIRONMENT (USING THE EXAMPLE OF PRESCHOOL EDUCATIONAL ORGANIZATIONS) - Ирина Игоревна Новикова; Наталья Федоровна Чуенко; Олег Андреевич Савченко; Евгений Анатольевич Новиков (Медицина в Кузбассе)
The problem of air pollution in organizations with long-term stay of children remains quite relevant and, despite the detailed study of the problem by a number of authors and the introduction of progressive engineering solutions in terms of the development and practical use of modern ventilation systems, still remains significant for pre-school education. Having studied the experience and achievements of domestic and foreign scientists, it was determined that the use of indoor plants can become a promising and budgetary direction for reducing the risk to children's health in organized groups. The purpose of the study is to substantiate the specific and quantitative selection of indoor plants to improve the air environment in organized children's groups and to develop recommendations for their use. Material and methods. Among the numerous assortment of indoor plants, the most suitable for preschool institutions were identified. The dimensions of the selected plants were determined by the metric method, as well as the area of the leaf apparatus was determined. Air sampling was carried out during the working week. Measurements of microclimate parameters were carried out in all studied group cells. The gas-absorbing capacity of indoor plants was studied in laboratory conditions in seed chambers with a volume of. Results and their discussion. In the groups where plants were present, the indicators of the total number of microorganisms varied from 350 to 1200 CFU/m3. The average values of relative humidity (in %) in all group cells were below the lower limit of the hygienic standard regulated by SanPiN 1.2.3685-21 for children (40-60 %). With a formaldehyde concentration equal to 3 MPC, one Chlorophytum comosum plant will need 38 hours to reduce it to a regulated value of 0.01 MPC; Sansevieria trifasciata will take 24 hours; Cyperus alternifolius will take 27 hours, n = 1200. Conclusion. When placing an assortment of indoor plants in a preschool organization with pronounced phytoncidal and transpiring properties, it leads to a steady decrease in the total number of microorganisms and an increase in air humidity. Analysis of the composition of the air in the inhalation seed chambers showed that in the presence of plants, the concentration of formaldehyde decreases.